Maintenance vs. Manipulation in Auditory Verbal Working Memory in the Elderly: New Insights Based on Temporal Dynamics of Information Processing in the Millisecond Time Range - Jablonska, Katarzyna; Piotrowska, Magdalena; Bednarek, Hanna; Szymaszek, Aneta; Marchewka, Artur; Wypych, Marek; Szelag, Elzbieta (Frontiers in Aging Neuroscience, 2020)
Working memory (WM) is a limited-capacity cognitive system which allows the storage and use of a limited amount of information for a short period of time. Two WM processes can be distinguished: maintenance (i.e., storing, monitoring, and matching information) and manipulation (i.e., reordering and updating information). A number of studies have reported an age-related decline in WM, but the mechanisms underlying this deterioration need to be investigated. Previous research, including studies conducted in our laboratory, revealed that age-related cognitive deficits are related to decreased millisecond timing, i.e., the ability to perceive and organize incoming events in time. The aim of the current study was (1) to identify in the elderly the brain network involved in the maintenance and manipulation WM processes, and (2) to use an fMRI task to investigate the relation between the brain activity associated with these two processes and the efficiency of temporal information processing (TIP) on a millisecond level reflected by psychophysical indices. Subjects were 41 normal healthy elderly people aged from 62 to 78 years. They performed: (1) an auditory verbal n-back task for assessing WM efficiency in an MRI scanner and (2) a psychophysical auditory temporal-order judgment task for assessing temporal resolution in the millisecond domain outside the scanner. The n-back task comprised 3 conditions (0-, 1-, and 2-back), which allowed maintenance (1- vs 0-back comparisons) and manipulation (2- vs 1-back comparisons) processes to be distinguished. Results revealed the involvement of a similar brain network in the elderly to that found in previous studies. However, during maintenance processes we found relatively limited and focused activations which were significantly extended during manipulation. A novel result of our study, never reported before, is an indication of significant moderate correlations between the efficiency of WM and TIP. These correlations were found only for manipulation, but not for maintenance. Our results confirmed the hypothesis that manipulation in the elderly is a dynamic process requiring skilled millisecond timing with high temporal resolution. We conclude that millisecond timing contributes to WM manipulation in the elderly, but not to maintenance.